Применение антибактериальных паст при эндодонтическом лечении деструктивных форм хронического периодонтита (Эндодонтия Today, 2020)
This work describes a clinical study and a treatment of destructive forms of chronic periodontitis in 98 patients. The patients were divided into two groups. The first group received an endodontic treatment with paste "Metapex" and in the second group with "Chitosan with silver". The use of the latter one made possible to effect reliably the antiseptic treatment and to accelerate the regeneration of bone tissue and to achieve in 12 months the complete destruction of the ossification focus periapical region of teeth in 92,9% of patients.